Efficacy of 18F-fluorodeoxyglucose PET/CT for Detecting Lymph Node Metastasis in Papillary Thyroid Carcinoma. Issue 3 (July 2018) - Lee, Dong Won; Song, Chang Myeon; Ji, Yong Bae; Kim, Ji Young; Choi, Yun Young; Lee, Ji Young; Tae, Kyung
Objective: To evaluate the efficacy of preoperative 18 F-fluorodeoxyglucose positron emission tomography/computed tomography (PET/CT) for detecting cervical lymph node (LN) metastasis in papillary thyroid carcinoma (PTC). Study Design: Case series with chart review. Setting: University tertiary care facility. Subjects and Methods: We retrospectively compared the pathologic results for 409 cervical LN levels in 140 patients who underwent thyroidectomy and central neck dissection with/without lateral neck dissection with the findings of preoperative PET/CT, ultrasonography (US), and CT. We judged LN metastasis in PET/CT using the maximum standardized uptake value (SUVmax) at the optimal cutoff value in receiver operating characteristic curves and compared the sensitivity, specificity, and diagnostic accuracy of the 3 imaging tools. Results: At all neck levels (central and lateral compartments), PET/CT had a sensitivity of 57.5%, specificity of 68.6%, and diagnostic accuracy of 63.6% when the cutoff value of SUVmax was 1.125. The corresponding values were 59.1%, 90.6%, and 76.3%, respectively, for US and 53.8%, 91.9%, and 74.6% for CT. In the central compartment (level VI), sensitivity, specificity, and diagnostic accuracy were 48.9%, 67.4%, and 59.9% for PET/CT (cutoff SUVmax 1.125); 47.8%, 96.3%, and 76.7% for US; and 41.3%, 97.0%, and 74.4% for CT, respectively. In the lateral compartment (levels II-V), the corresponding values of sensitivity, specificity, and diagnostic accuracy were 70.2%, 69.3%, and 69.8% for PET/CT (cutoff SUVmax 1.055); 70.2%, 81.8%, and 75.8% for US; and 65.9%, 84.1%, and 74.7% for CT. Conclusion: PET/CT is less effective as a preoperative diagnostic tool for detecting cervical lymph node metastasis in PTC than US or CT.